Does school socioeconomic composition matter more in some countries than others, and if so, why?. Issue 1 (2nd January 2022) - Sciffer, Michael G.; Perry, Laura B.; McConney, Andrew
ABSTRACT: International research has consistently found that the socioeconomic segregation of schools may worsen inequalities in schooling outcomes through the socioeconomic compositional effect. This study examines whether the socioeconomic compositional effect varies between developed countries and potential mechanisms by which national schooling systems moderate its effect. The results suggest that the socioeconomic compositional effect does vary between developed countries and that national differences in its size were partially explained by policies of tracking age and the proportion of students that attend public schools. We conclude schooling systems in developed countries would require substantial reform to reduce the detrimental effects of school composition on disadvantaged students.